Sistem Informasi Raport Online Pada Mts Minhajut Tholibin Jakarta Barat - Heru Anang Setiawan; Maruloh Maruloh (STMIK Pringsewu, 2022)
Schools have not fully utilized technological developments in processing data such as student data, teacher data, student attendance, and student report cards, and have not been integrated with the school system due to the lack of an academically adaptable application system. The use of media or dissemination of information is still done by pasting pamphlets on the walls of magazines, as well as storing academic data in archives in a form that is difficult to find. This is considered less effective in school management, given the rapid development of technology today. With the problems that the authors found, an online report card information system application will be designed using the Waterfall method, to make it easier to manage administrative and academic data to be more organized in decision-making in the school environment.